In vitro effect of hydroxychloroquine on pluripotent stem cells and their cardiomyocytes derivatives - Kamga Kapchoup, Michelle Vanessa; Hescheler, Jürgen; Nguemo, Filomain (Frontiers in Pharmacology, 2023)
Hydroxychloroquine (HDQ) is an antimalarial drug that has also shown its effectiveness in autoimmune diseases. Despite having side effects such as retinopathy, neuromyopathy and controversial cardiac toxicity, HDQ has been presented and now intensively studied for the treatment and prevention of coronavirus disease 2019 (COVID-19). Recent works revealed both beneficial and toxic effects during HDQ treatment. The cardiotoxic profile of HDQ remains unclear and identifying risk factors is challenging. Here, we used well-established cell-cultured to study the cytotoxic effect of HDQ, mouse induced pluripotent stem cells (miPSC) and their cardiomyocytes (CMs) derivatives were exposed to different concentrations of HDQ. Cell colony morphology was assessed by microscopy whereas cell viability was measured by flow cytometry and impedance-based methods. The effect of HDQ on beating activity of mouse and human induced pluripotent stem cell-derived CMs (miPSC-CMs and hiPSC-CMs, respectively) and mouse embryonic stem cell-derived CMs (mESC-CMs) were captured by the xCELLigence RTCA and microelectrode array (MEA) systems. Our results revealed that 20µM of HDQ promotes proliferation of stem cells used suggesting that if appropriately monitored, HDQ may have a cardioprotective effect and may also represent a possible candidate for tissue repair. In addition, the field potential signals revealed that higher doses of this medication caused bradycardia that could be reversed with a higher concentration of ß-adrenergic agonist, Isoproterenol (Iso). On the contrary, HDQ caused an increase in the beating rate of hiPSC-CMs, which was further helped upon application of Isoproterenol (Iso) suggesting that HDQ and Iso may also work synergistically. These results indicate that HDQ is potentially toxic at high concentrations and can modulate the beating activity of cardiomyocytes. Moreover, HDQ could have a synergistic inotropic effect with isoproterenol on cardiac cells.